Proton wave propagation along collagen fibers - Pedro Costa; Anna Maznichenko; Noam Agmon; Peter Pohl (European Biophysics Journal, 2026)
Collagen deposition and alignment in the tumor stroma stiffen the extracellular matrix and, via integrin signaling, stimulate proton extrusion by cancer cells. In aggressive tumors, migration occurs preferentially along aligned collagen fibers, where proton efflux at the leading edge acidifies and degrades the matrix to facilitate invasion. Whether directional proton diffusion along collagen fibers exacerbates invasion remains uncertain, as it is not known how far protons can travel along a fiber before being released. To characterize the release barrier, we labeled collagen lysine side chains with a pH-sensitive fluorescein derivative and introduced an interfacial proton flux by microinjecting HCl near the surface of self-assembled collagen fibers elevated above the chamber bottom. Proton wave propagation was monitored by wide-field fluorescence microscopy. Quantitative analysis of the fluorescence transients revealed that proton migration is best described by a one-dimensional diffusion model with a finite surface-to-bulk release rate. A single global parameter set consistently described all experiments. From the fitted release rate, we determined a Gibbs activation energy barrier Δ G ‡ of approximately 30 k B T , comparable to values reported for membrane–water interfaces. These results demonstrate that protons can travel tens of micrometers along collagen fibers before equilibrating with the bulk solution, suggesting that membrane-anchored collagen fibers may provide an effective pathway for directing acidification along migration tracks in tumor stroma.

Cysteine-mediated structural stabilization of the tetrameric GlpF - Christine Siligan; Sascha Gratzl; Kristyna Pluhackova; Nikolaus Goessweiner-Mohr; Peter Pohl; Andreas Horner (European Biophysics Journal, 2025)
The stability of membrane proteins depends on amino acid-specific interactions within the protein structure, its surroundings, e.g. the lipid membrane and ionic solutions, and their substrates. A molecular understanding of the factors affecting protein stability is essential for comprehending the respective structure–function relationships. This study aims to investigate the influence of native cysteine residues, ions, and glycerol on the stability of GlpF, the aqua(glycerol)porin of E. coli , under well-controlled conditions. To this end, the wild-type protein and its variant with four cysteine residues in the transmembrane helix bundle mutated to glycines were overexpressed and purified. The thermal unfolding of GlpF occurs at a transition temperature of 59.2 ± 1.4 °C, corresponding to an apparent Gibbs free energy of unfolding of approximately 10 kcal/mol. In contrast to the wild-type protein, the mutated GlpF exhibits a second unfolding transition, lowered by approximately 10 °C, and a decreased Gibbs free energy of unfolding of 5 kcal/mol. Our findings highlight that divalent ions and glycerol have a more pronounced stabilizing effect on the mutated GlpF than the wild-type protein. The structural consequences of cysteine to glycine mutations in terms of transmembrane helix rearrangement, the inter- and intra-chain H-bond network, and the reduced inter-chain interaction free energy, as well as intra-chain electrostatic energy and van der Waals energy, are revealed by molecular dynamics simulations. In conclusion, our findings illustrate the significance of cysteine residues distant from each other on protein oligomerization and stability, and the amplified impact of (de)stabilizing agents on less stable protein variants.

Immunologically active cell wall polysaccharides of green microalga Dictyosphaerium chlorelloides (Chlorellacea) - Leonid Sushytskyi; Andriy Synytsya; Pavol Lukáč; Lenka Rajsiglová; Peter Capek; Radek Pohl; Roman Bleha; Luca E. Vannucci; Daniel Smrz; Jana Čopíková; Petr Kaštánek (Carbohydrate Polymers, 2025)

Revisiting the sustainability science research agenda - Mesfin Sahle; Shruti Ashish Lahoti; So-Young Lee; Katja Brundiers; Carena J. van Riper; Christian Pohl; Herlin Chien; Iris C. Bohnet; Noé Aguilar-Rivera; Peter Edwards; Prajal Pradhan; Tobias Plieninger; et al. (Sustainability Science, 2025)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Photodynamic activity rather than drilling causes membrane damage by a light-powered molecular nanomotor - Alexander M. Firsov; Juergen Pfeffermann; Anton S. Benditkis; Tatyana I. Rokitskaya; Anton S. Kozlov; Elena A. Kotova; Alexander A. Krasnovsky; Peter Pohl; Yuri N. Antonenko (Journal of Photochemistry and Photobiology B: Biology, 2023)

Clinical features of migraine with onset prior to or during start of combined hormonal contraception: a prospective cohort study - Gabriele S. Merki-Feld; Peter S. Sandor; Rossella E. Nappi; Heiko Pohl; Christoph Schankin (Acta Neurologica Belgica, 2022)
Many studies have described the features of menstrually related migraines but there is a lack of knowledge regarding the features of migraine in combined hormonal contraceptive users (CHC). Hormone-withdrawal migraines in the pill-free period could differ from those in the natural cycle. Gynaecologic comorbidities, like dysmenorrhea and endometriosis, but also depression or a family history might modify the course of migraine. A better understanding of migraine features linked to special hormonal situations could improve treatment. For this prospective cohort study, we conducted telephone interviews with women using a CHC and reporting withdrawal migraine to collect information on migraine frequency, intensity, triggers, symptoms, pain medication, gynaecologic history and comorbidities ( n = 48). A subset of women agreed to also document their migraines in prospective diaries. The mean number of migraine days per cycle was 4.2 (± 2.7). Around 50% of these migraines occurred during the hormone-free interval. Migraine frequency was significantly higher in women who suffered from migraine before CHC start (5.0 ± 3.1) ( n = 22) in comparison to those with migraine onset after CHC start (3.5 ± 2.1) ( n = 26). Menstrually related attacks were described as more painful (57.5%), especially in women with migraine onset before CHC use (72%) ( p , hormone-withdrawal migraines in CHC users are very intense and the response to acute medication is less good, especially in those women, who developed migraine before CHC use.

Biophysical Reviews’ “Meet the Councilor Series”—a profile of Peter Pohl - Peter Pohl (Biophysical Reviews, 2021)
It is my pleasure to write a few words to introduce myself to the readers of Biophysical Reviews as part of the “Meet the Councilor Series.” Currently, I am serving the second period as IUPAB councilor after having been elected first in 2017. Initially, I studied Biophysics in Moscow (Russia) and later Medicine in Halle (Germany). My scientific carrier took me from the Medical School of the Martin Luther University of Halle-Wittenberg, via the Leibniz Institute for Molecular Pharmacology (Berlin) and the Institute for Biology at the Humboldt University (Berlin) to the Physics Department of the Johannes Kepler University in Linz (Austria). My key research interests lie in the molecular mechanisms of transport phenomena occurring at the lipid membrane, including (i) spontaneous and facilitated transport of water and other small molecules across membranes in reconstituted systems, (ii) proton migration along the membrane surface, (iii) protein translocation, and (iv) bilayer mechanics. Training of undergraduate, graduate, and postdoctoral researchers from diverse academic disciplines has been—and shall remain—a consistent part of my work.

The energetic barrier to single-file water flow through narrow channels - Juergen Pfeffermann; Nikolaus Goessweiner-Mohr; Peter Pohl (Biophysical Reviews, 2021)
Various nanoscopic channels of roughly equal diameter and length facilitate single-file diffusion at vastly different rates. The underlying variance of the energetic barriers to transport is poorly understood. First, water partitioning into channels so narrow that individual molecules cannot overtake each other incurs an energetic penalty. Corresponding estimates vary widely depending on how the sacrifice of two out of four hydrogen bonds is accounted for. Second, entropy differences between luminal and bulk water may arise: additional degrees of freedom caused by dangling OH-bonds increase entropy. At the same time, long-range dipolar water interactions decrease entropy. Here, we dissect different contributions to Gibbs free energy of activation, Δ G ‡ , for single-file water transport through narrow channels by analyzing experimental results from water permeability measurements on both bare lipid bilayers and biological water channels that (i) consider unstirred layer effects and (ii) adequately count the channels in reconstitution experiments. First, the functional relationship between water permeabilities and Arrhenius activation energies indicates negligible differences between the entropies of intraluminal water and bulk water. Second, we calculate Δ G ‡ from unitary water channel permeabilities using transition state theory. Plotting Δ G ‡ as a function of the number of H-bond donating or accepting pore-lining residues results in a 0.1 kcal/mol contribution per residue. The resulting upper limit for partial water dehydration amounts to 2 kcal/mol. In the framework of biomimicry, our analysis provides valuable insights for the design of synthetic water channels. It thus may aid in the urgent endeavor towards combating global water scarcity.

Detection of Cryptosporidium spp. Infection in Wild Raccoons (Procyon lotor) from Luxembourg Using an ELISA Approach - Mike Heddergott; Alain C. Frantz; Daniel Pohl; Natalia Osten-Sacken; Peter Steinbach (Acta Parasitologica, 2020)

MRI-based prediction of conversion from clinically isolated syndrome to clinically definite multiple sclerosis using SVM and lesion geometry - Kerstin Bendfeldt; Bernd Taschler; Laura Gaetano; Philip Madoerin; Pascal Kuster; Nicole Mueller-Lenke; Michael Amann; Hugo Vrenken; Viktor Wottschel; Frederik Barkhof; Stefan Borgwardt; Stefan Klöppel; et al. (Brain Imaging and Behavior, 2019)

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)

Driving Forces of Translocation Through Bacterial Translocon SecYEG - Denis G. Knyazev; Roland Kuttner; Mirjam Zimmermann; Ekaterina Sobakinskaya; Peter Pohl (The Journal of Membrane Biology, 2018)

The mediating role of cortical thickness and gray matter volume on sleep slow-wave activity during adolescence - Aimée Goldstone; Adrian R. Willoughby; Massimiliano de Zambotti; Peter L. Franzen; Dongjin Kwon; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan; Eva M. Müller-Oehring; Devin E. Prouty; Brant P. Hasler; Duncan B. Clark; et al. (Brain Structure and Function, 2018)

Structural Features and Anti-coagulant Activity of the Sulphated Polysaccharide SPS-CF from a Green Alga Capsosiphon fulvescens - Andriy Synytsya; Doo Jin Choi; Radek Pohl; Ye Seul Na; Peter Capek; Erika Lattová; Tomáš Taubner; Ji Won Choi; Chang Won Lee; Jae Kweon Park; Woo Jung Kim; Sung Min Kim; et al. (Marine Biotechnology, 2015)

The missing “link”: an autosomal recessive short stature syndrome caused by a hypofunctional XYLT1 mutation - Julia Schreml; Burak Durmaz; Ozgur Cogulu; Katharina Keupp; Filippo Beleggia; Esther Pohl; Esther Milz; Mahmut Coker; Sema Kalkan Ucar; Gudrun Nürnberg; Peter Nürnberg; Joachim Kuhn; et al. (Human Genetics, 2014)

Why longer song elements are easier to detect: threshold level-duration functions in the Great Tit and comparison with human data - Nina U. Pohl; Hans Slabbekoorn; Heinrich Neubauer; Peter Heil; Georg M. Klump; Ulrike Langemann (Journal of Comparative Physiology A, 2013)

Microinjection in combination with microfluorimetry to study proton diffusion along phospholipid membranes - Yuri N. Antonenko; Peter Pohl (European Biophysics Journal, 2008)

Adsorption of Radionuclides (134Cs, 85Sr, 226Ra, 241Am) by Extracted Biomasses of Cyanobacteria (Nostoc Carneum, N. Insulare, Oscillatoria Geminata and Spirulina Laxis-Sima) and Phaeophyceae (Laminaria Digitata and L. Japonica; Waste Products from Alginate Production) at Different pH - Peter Pohl; Wolfgang Schimmack (Journal of Applied Phycology, 2006)

Membrane destabilization by ricin - Jan Sun; Elena E. Pohl; Oxana O. Krylova; Eberhard Krause; Igor I. Agapov; Alexander G. Tonevitsky; Peter Pohl (European Biophysics Journal, 2004)

Overwintering of genetically modified sugar beet, Beta vulgaris L. subsp. vulgaris, as a source for dispersal of transgenic pollen - Matthias Pohl-Orf; Ulrike Brand; Sarah Drießen; Peter René Hesse; Marcus Lehnen; Claudia Morak; Thomas Mücher; Christiane Saeglitz; Cornelia von Soosten; Detlef Bartsch (Euphytica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Genetic engineering of recombinant glycoproteins and glycosylation pathway in mammalian host cells - Eckart Grabenhorst; Peter Schlenke; Susanne Pohl; Manfred Nimtz; Harald S. Conradt (Glycoconjugate Journal, 1999)

Chloroplast DNA and isozyme evidence on the evolution ofSenecio vulgaris (Asteraceae) - Hans Peter Comes; Joachim W. Kadereit; Andreas Pohl; Richard J. Abbott (Plant Systematics and Evolution, 1997)